NDOLA‐2, a high‐yielding, open‐pollinated conventional spring type canola in North Dakota. Issue 1 (9th December 2021) - Rahman, Mukhlesur; Mendoza, Luis E. Río; Anderson, James V.; Berhow, Mark; Roy, Jayanta; Eriksmoen, Eric; Miller, Meridith; Pradhan, Gautam; Rickertsen, John; Ostlie, Mike; Hanson, Bryan
Abstract: NDOLA‐2 (Reg. no. GP‐9, PI 698655) is an open‐pollinated, non–genetically modified, spring‐type canola ( Brassica napus L.) developed at North Dakota State University (NDSU) and approved for specialty release by the North Dakota Agricultural Experiment Station. NDOLA‐2 was tested as experimental line NDC‐E16198 from 2017 to 2020 (16 location‐years) in NDSU canola breeding nurseries and in 2019 and 2020 (8 location‐years) in North Dakota Canola Variety Trials (ND‐CVTs). NDOLA‐2 has been identified as a germplasm with higher seed yield potential and disease tolerance. NDOLA‐2 had 5.5% higher seed yield and 2.1% lower oil contents compared with those of commercial hybrid checks in NDSU canola breeding trials. Also, NDOLA‐2 had 5.4% higher seed yield and 1.6% lower oil content over the means of commercial cultivars/hybrids in ND‐CVTs. It has been identified as resistant to blackleg disease (Pathogenicity Group 4) and Sclerotinia stem rot disease of canola. NDOLA‐2 flowers within 44 d from seeding, has a flowering period that lasts 22 d, and reaches maturity within 93 d from seeding with plants that are 103 cm tall. It is resistant to lodging, with a score of 2.1 out of 9, and has an overall breeder score of 8.0, where the trial mean score for all locations was 7.7.